A Comparative study of Early Childhood Education majors in Chile in the scenario of curricular updating - Calzadilla Pérez , Oscar Ovidio; Erices Quezada , Alicia Edith; Carvajal Donari , Constanza Andrea (Transformación, 2024)
Objective: The article ventures into the updating of university curricula for teacher training as a challenge in facing 2030 Educational Goals and the Sustainable Development Objectives. For this reason, a comparative study of early childhood education majors in Chile is presented together with a theoretical framework of the process of diagnosing the curricular updating experience of the Catholic University of Temuco Early Childhood Education major staff.Methods: A qualitative methodology based on the compared studies was used, which involved the application of inclusion and exclusion criteria. For this reason, methods of the theoretical level are triangulated (analytical-synthetic, inductive-deductive and transition from the abstract to the concrete). At the empirical level, the analysis of documents was used as an essential method that gives priority to the study of research and curricular references in open access of the seven majors of the sample. At the statistical level, procedures based on the construction of tables were used.Results: The main findings include a typology of the levels of accreditation, the profiles and object of the profession, the definition of labor fields, values, the approach to competencies, the tendency to conceive mentions as a specialization teaching resource, the duration, daily activity types, the training modality and the organization of the training itinerary.Conclusion: The authors arrived at the conclusion that several tasks for the elaboration of a new study plan are recommendable, giving priority to the logical-didactic organization of pedagogical training courses and the treatment of comprehensive courses.
Keywords: higher education; early childhood education; teacher profession; college curriculum